Influence of background resonance radiation on hepatic glycogen levelin chronic opisthorchiasis invasion - O. A. Poddoubnaya; E. I. Beloborodov; Ye. F. Levitsky (Бюллетень сибирской медицины, 2007)
Chronic opisthorchiasis is human parasitologic disease with signs of decreased reactivity of the organism. One of the ways to assess the organism reactivity is qualitative and quantitative analysis of glycogen in hepatic cells. Decreased glycogen level is a sign of decreased adaptation possibilities and manifests in disregulation of adaptation reactions. Experimental studies in vivo (model of chronic opisthorchiasis) revealed favorable influence of the background resonance radiation on the glycogen level in hepatic cell which indirectly points to increased reactivity of the organism which in turn may contribute to the maintenance of hepatic morphologic-functional status of full value and to prevent possible overstrain of its reserve possibilities.